The big book of knitted monsters : mischievous, lovable toys - Danger, Rebecca (Martingale, 2011)
Popular designer Danger presents 20 patterns for the most adorable monsters ever to climb off a pair of knitting needles. Each stuffie comes with complete instructions and how-to photos.